Efficacy and safety of Rhodiola crenulata extract in the treatment of acute high altitude disease, based on studies involving populations in China: A systematic review and meta-analysis - Gao, Zixuan; Liu, Yaoyuan; Liao, Weiwen; Song, Wenting; Zhang, Xinyi; Lin, Hanqing; Zhang, Han; Zhang, Tao; Pang, Wentai (Frontiers in Pharmacology, 2025)
IntroductionTo evaluate the efficacy and safety of Rhodiola crenulata extract (RCE) for the treatment of patients with acute high altitude disease (AHAD).MethodsThis study systematically retrieved randomized controlled trials (RCTs) published prior to September 2024 from eight distinct databases. It included AHAD patients, with the control group receiving either conventional western medicine (WM) or placebo, and the experimental group receiving RCE alone or in conjunction with WM. The primary outcomes were arterial oxygen saturation (SaO2) and arterial partial pressure of oxygen (PaO2). The secondary outcomes were total clinical efficacy, systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR). Adverse events incidence was analyzed to assess safety. The meta-analysis was performed with Review Manager 5.4, and the evidence’s certainty was assessed using the GRADE approach.ResultsThis study included 19 eligible RCTs with 1,690 participants. In improving SaO2, PaO2 and total clinical efficacy, no significant differences were found between RCE and WM, but RCE was more effective than placebo. RCE showed no significant effect in reducing SBP, DBP and HR. Regarding safety, the experimental group demonstrated superior performance compared to the control group.ConclusionRCE may enhance blood oxygen levels and mitigate clinical symptoms in the treatment of AHAD with favorable safety. Nonetheless, it is imperative to undertake further rigorous RCTs to validate these findings.Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/myprospero, identifier CRD42024593081.